Comorbidity Burden in Chronic Thromboembolic Pulmonary Hypertension: Implications and Outcome - Kilickiran Avci, Burcak; Basarici, Ibrahim; Akbulut, Mehmet; Atas, Halil; Yaylali, Yalin Tolga; Sinan, Umit Yasar; Ongen, Zeki (Mdpi, 2025)
Background and Objectives: Comorbidities, the coexistence of additional conditions with a primary disease, are increasingly prevalent, complicating disease management and clinical outcomes. While CTEPH is a well-studied condition in terms of risk factors and outcomes, the specific impact of comorbidity burden on clinical presentation, treatment decisions, and survival remains insufficiently explored. This study aims to assess the prevalence and burden of comorbidities in CTEPH and to examine their associations with initial clinical characteristics, treatment allocation, and survival, stratified by pulmonary endarterectomy (PEA) status. Materials and Methods: We included 187 CTEPH patients from eight tertiary PH centers (2009-2020). Cardiovascular and non-cardiovascular comorbidities were identified and categorized as 0, 1-2, or >= 3. Their impact on baseline six-minute walk distance (6MWD), hemodynamic parameters, operability decision, and survival was assessed. Results: Comorbidities were prevalent (90%), with 49% of patients having three or more. Hypertension, diabetes, coronary artery disease, and chronic kidney disease (CKD) were associated with lower 6MWD. Hypertension, atrial fibrillation, left heart failure, and CKD were linked to elevated right atrial and pulmonary arterial wedge pressures. Comorbidities rendered 39% of anatomically operable patients ineligible for surgery. No single comorbidity predicted survival. Among PEA patients, those with >= 3 cardiovascular comorbidities had worse survival (p = 0.010). In contrast, the comorbidity burden did not impact survival in non-PEA patients. PEA surgery (HR 0.342, 95% CI 0.130-0.899, p = 0.030) and baseline 6MWD (HR 0.997, 95% CI 0.994-1.000, p = 0.036) were identified as independent predictors of mortality. Conclusions: A high comorbidity burden is common in CTEPH and influences functional status, hemodynamics, and operability decisions. It may worsen long-term outcomes after PEA but appears to be less prognostic in non-operated patients, where disease severity seems to be the primary determinant of outcomes. These findings underscore the importance of careful operability assessment and proactive comorbidity management.
Keywords: chronic thromboembolic pulmonary hypertension; comorbidity; comorbidity burden; pulmonary endarterectomy; survival